Subclinical liver disease in volunteer blood donors with antibodies against hepatitis C (Colombia Medica, 1994)
To demonstrate the relationship between antibodies to hepatitis C virus (anti-VHC) and hepatic disease in blood donors, a prospective study was carried out in 18 donors with anti-VHC-positive ELISA 2nd generation with clinic history negative for alcoholism, obesity, hepatotoxic drugs, and history of hepatitis, with serologic test negative for virus B hepatitis and without clinic and biochemical changes of hepatic disease. In the transcutaneous hepatic biopsy were found 3 hepatic fatties, four cholestasis, two persistent chronic hepatitis, and one cirrhosis, while the 8 ( 44%) remaining patients were normal. This paper shows that the positive for anti-VHC may identify a group of apparently healthy donors with subclinical hepatic disease.